Pengaruh Model Pembelajaran Problem Based Learning dalam Pembelajaran Pendidikan Kewarganegaraan terhadap Kemampuan Berpikir Kritis Mahasiswa - Taty Rosiana Koroh; Petrus Ly (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This study aims to determine the implementation of model learning problem based learning in citizenship education of national integrity material to students critical thinking ability. This research uses a quantitative approach. Sample determination using random sampling clusters. This study was imposed on students of the second semester of primary school teacher Education Program, Nusa Cendana University. The selected sample is Class II A as an experimental class of 24 students and class II B as a control class as many as 25 students. The instrument used in the form of observation guidelines and a test is about the description to measure the student's critical thinking ability. Data obtained in the form of pretests and posttest values. The Data was analyzed using SPSS 16.0 to see test normality and test homogeneity as prerequisite test then continued with Test T. Results obtained from the test of normality (Kolmogorov-Smirnov test) is the value of Sig 0138 (> 0.05) which shows the sample data derived from the population of normal and homogeneity test (test Levene) is 0322 (> 0.05) which shows the value of Posttest uniform and the significance value of T-Test 0.000 (< 0.05 Learning problem based learning on the ability of critical thinking.